Peran Guru dalam Membangun Lingkungan Belajar Efektif pada Pembelajaran Matematika (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2022)
The teacher is responsible for designing learning to guide students according to the goals that have been set. Through the learning process, in addition to developing intellectual abilities, students are expected to develop all their personal abilities so that they can learn well. As a teacher, the author needs to carry out his role to create an effective learning environment so that students can develop themselves well. Therefore, the purpose of writing this scientific paper is to analyze the role of the teacher in creating an effective learning environment so that students can learn to develop their abilities and learn mathematics well. The method used in this research is descriptive qualitative method, namely by examining problems in the field in actual conditions and developing solutions based on the practice of field experience. The results showed that the effective learning environment created by the teacher supports students to learn to develop their abilities so that they can learn mathematics well. So, it can be concluded that the effective learning environment has a good impact on learning mathematics.
Keywords: teacher’s role; learning environments; effective